The efficacy of skin care products containing glutathione in delivering skin lightening in Indonesian women - Kristiana Etnawati; Dwi Retno Adiwinarni; Devi Artami Susetiati; Yusuke Sauchi; Hitomi Ito (PAGEPress Publications, 2019)
Glutathione is a potent antioxidant, which is widely used in skin care products for skin lightening especially in the Asian market. Presently, there was only one study of topical 2% oxidized glutathione (GSSG) in Philipino women, further study is needed to evaluate the efficacy and safety of cosmetic products containing glutathione. A double blind randomized clinical trial study was conducted in Yogyakarta, Indonesia, in 74 healthy Indonesian women, with average age 33.3 ± 5.9 years when subjects participated in the study. Each subject received supervised applications of Facial Wash twice a day, Day Cream with sunscreen and Night Cream. The subjects were divided into 3 groups based on the active ingredients of the tested products, which included glutathione reduced (GSH) 0.1%, GSH 0.5%, and without GSH. The effects of the tested products in lightening skin color and pigmentation were measured colorimetry with Chromameter Minolta for L*. Compared to a baseline, there were significant increases of L* (lightness) or ΔL* detected as early as week 2 in which group of GSH 0.1% were significantly higher compared to group of GSH 0.5% and group without GSH. Hyperpigmented lesions also improved, where GSH 0.5% group showed its superiority compared to others groups in week 8. The undesired effect were few minutes mild tingling sensation after night cream, and worsening of acne in all tested products. Conclusion skin care products containing GSH 0.1% and 0.5% were effective in facial skin lightening.